Kedudukan Keputusan Internal Partai Politik dalam Pencalonan Kepala Daerah dan Relevansinya sebagai Objek Sengketa di Peradilan Tata Usaha Negara - Aisyah Shobuhah (Universitas Kuningan, 2025)
Political parties in Indonesia play a crucial role in nominating regional head candidates through the issuance of recommendation letters based on each party’s (AD/ART). However, this practice frequently leads to disputes because the regional election process itself is strictly governed by Law Number 10 of 2016. This study examines the legal status of these recommendation letters within the state administration system and assesses whether internal party decisions can be subjected to litigation at the State Administrative Court (PTUN). The analysis focuses on Padang PTUN Decision Number 21/G/2015/PTUN-PDG, in which a lawsuit against a recommendation letter issued by the Gerindra (DPP) was rejected for failing to meet the legal criteria of a State Administrative Decision (KTUN).Using a normative juridical approach, this study finds that internal party decisions are inherently private because they are made by organisational administrators based on internal regulations rather than by public officials executing governance. Consequently, party recommendation letters fall outside the absolute competence of the PTUN, which only possesses the jurisdiction to review concrete, individual, and final actions derived from statutory authority. This paper highlights the tension between political party autonomy, as stipulated in Law Number 2 of 2011, and the need for public legal certainty. Therefore, disputes related to candidate recommendations must be resolved through the internal Party Court (Mahkamah Partai) first to ensure local democratic processes continue without disrupting state administration.